Response to Wysocki’s Rejoinder to Block on indifference - Block, Walter (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2024)
Wysocki (2024) is a critique of Block (2022). The present paper is a response to the former. We are in effect debating the best reaction to Nozick (1977) which criticized Austrian economics on the ground that it makes two claims that are incompatible with one another. On the one hand, the praxeological school is noted for its aversion to the concept of indifference. On the other hand, the Austrian school also accepts supply and demand curves, and diminishing marginal utility. These three concepts imply homogeneous elements that comprise them. But if they are truly homogeneous, people ought to be indifferent between the different elements of them. Hence, the tension, not to say logical contradiction, in this perspective. Block (1980) was an attempt to respond to Nozick (1977). Hoppe (2005a,b; 2009) and Wysocki (2016; 2017; 2021; 2024) who supports Hoppe, maintain that Block’s refutation of Nozick (1977) was not efficacious at all, at worst, or at best, certainly not fully successful.Specifically, Wysocki maintains that there is a bifurcation between choosing and preferring; for example, no one is even aware of which foot goes first when entering a restaurant, and, yet, one has to make a choice about it. He avers that it is entirely possible to prefer to save either son, equally, while actually picking one, and not the other.
Keywords: indifference; supply and demand; diminishing marginal utility; subjectivism; behaviorism; psychologizing; preference